EU competition law and the financial services sector - Lista, Andrea (Abingdon, Oxon : Informa Law, 2013)
'Competition law is a complex and constantly evolving area of law which affects every aspect of the market economy, including the financial services sector. This book is a comprehensive and practical guide to the application of the EU competition rules to banking and insurance industries'--
Includes bibliographical references (pages 261-265) and index.
Keywords: Antitrust law -- European Union countries; Competition -- European Union countries; Financial services industry -- Law and legislation -- European Union countries